Prosedur Pengembangan Tes Hasil Belajar Standar: Dari Kisi-Kisi Hingga Perakitan Soal - Aprilia Mengga; Angreni Tamal Nenohai (Indo Publishing, 2026)
The procedure for developing standardized learning achievement tests is a systematic process aimed at producing evaluation instruments that are valid, reliable, and objective. The development stages begin with the preparation of a test blueprint as a guideline for determining competencies, materials, indicators, and levels of item difficulty. This is followed by item writing and review to ensure the appropriateness of the content, construction, language, and alignment with learning objectives and Bloom’s Taxonomy. The test is then piloted and analyzed to determine the level of difficulty, discriminating power, distractor effectiveness, validity, and reliability of the test items. Based on the analysis results, the items are revised, selected, and assembled into a test instrument ready for use. Through a structured procedure, standardized learning achievement tests can serve as accurate measurement tools for assessing students’ competency achievement